The Tradition of Cacap-Cacapan Marriage as Indonesian Literature Online Learning Materials For High School Students - Hartati Ratna Juita; Herlina Herlina; Sigit Widiyarto (STAI Hubbulwathan Duri, 2023)
The lack of literary material sourced from indigenous regional traditions is the cause of the weakness of literary learning in high school. The purpose of this study is to find out the meaning of what speeches are contained in the Cacap-cacapan tradition of Lubuk Linggau West Sumatra, and to find out the process of learning to be bold in literature for high school students. The method used was qualitative. Participants as informants involved in this study were the traditional cacap-cacapan event guide, the bride and groom, the bride's parents, the close family of the bride and groom, and invited guests. The research location was Lubuklinggau City which is at the same level as the western district in the province of South Sumatra. The results of prayer analysis in the Cacap-Cacapan tradition show that the meaning of traditional prayer utterances contains hope, advice and words of motivation for the bride and groom to live a good life material and analysis of the Cacap-Cacapan tradition prayer was used as an online literature study. The online learning process could use different platforms in one learning activity. Learning focused on student activities with the stages of informing, sharing, discussing and evaluating.